Measuring the hierarchy of molecular events during clathrin-mediated endocytosis - Loerke, Dinah (2011)
A well-orchestrated hierarchy of molecular events is required for successful initiation and maturation of clathrin-coated pits (CCPs). Nevertheless, CCPs display a broad range of lifetimes. This dynamic heterogeneity could either reflect differences in the temporal hierarchy of molecular events, or similar CCP maturation processes with variable kinetics. To address this question, we have used multi-channel image acquisition and automated analysis of CCP dynamics in combination with a new method to quantify the time courses of recruitment of endocytic factors to CCPs of different lifetimes. Using this approach we have extracted the kinetics of recruitment and disassembly of fluorescently labelled clathrin and/or AP-2 throughout the entire lifetime of temporally-defined CCP cohorts. Based on these analyses, we can (i) directly correlate recruitment profiles of these two proteins, (ii) define 5 distinct CCP maturation phases, i.e. initiation, growth, maturation, separation and departure, (iii) distinguish events with absolute versus fractional timing and (iv) provide information on the spatial distribution of fluorophores during CCP maturation. Emerging from these analyses is a more clearly defined role for AP-2 in determining the temporal hierarchy for clathrin recruitment and CCP maturation. This method provides a new means to identify other such hierarchies during CCP maturation.